Family Management on Children with Autism: A Phenomenological Study - Winarianti; Jiu, Cau Kim; Kardiatun, Tutur; Bhakti, Wida Kuswida (Indonesian Journal of Disability Studies, 2022)
Background: Children with autism had disorder in their physical, mental, and cognitive development and socialization function, which then brought burden in family care. Method: This research used phenomenological approach by involving three type families and was conducted in Pontianak, West Borneo. Result: This research found four themes in nuclear families: the role of parent in treatment of ASD, the role of nuclear family as a caregiver for ASD, the virtue of therapy for children and mood change as parent. Three themes in extended family: the role of parent in treatment of ASD, the role of extended family as a caregiver ASD and mood change as parent. Three themes in single parent: the role of single parent with ASD, the virtue of therapy for children and consequences as a single parent. Conclusion: Each type of family had differences of parenting pattern and burden level in treatment of autistic children.